Trends of Reforms in the Principles of Islamic Jurisprudence | اتجاهات التجديد في أصول الفقه - Iffatul Umniati Ismail (Al-Zahra : Journal for Islamic and Arabic Studies, 2009)
This article discusses about the development of Ushul Fiqh and the importanceof its reform as well as reform of Fiqh itself. The researcher describes somemethods of reform on Ushul Fiqh that brought by Muslim scholars such asradical and conservative methods. The researcher found advantage andinsufficient notes on those methods of reform and assesses the most correctedoutcome of those methods and offers new methodology of reform on Ushul Fiqhthat based on current condition and according to the how long it will givepositive result for the umah. Furthermore the researcher tries to relate betweenUshul Fiqh and modern knowledge and other methodologies that currently expanded